An analysis of the services provided by community health workers within an urban district in South Africa: a key contribution towards universal access to care - L. S. Thomas; E. Buch; Y. Pillay (BMC, 2021)
Abstract Introduction Community health worker teams are potential game-changers in ensuring access to care in vulnerable communities. Who are they? What do they actually do? Can they help South Africa realize universal health coverage? As the proactive arm of the health services, community health workers teams provide household and community education, early screening, tracing and referrals for a range of health and social services. There is little local or global evidence on the household services provided by such teams, beyond specific disease-oriented activities such as for HIV and TB. This paper seeks to address this gap. Methods Descriptive secondary data analysis of community health worker team activities in the Ekurhuleni health district, South Africa covering approximately 280,000 households with 1 million people. Results Study findings illustrated that community health workers in these teams provided early screening and referrals for pregnant women and children under five. They distributed condoms and chronic medication to homes. They screened and referred for hypertension, diabetes mellitus, HIV and TB. The teams also undertook defaulter and contact tracing, the majority of which was for HIV and TB clients. Psychosocial support provided was in the form of access to social grants, access to child and gender-based violence protection services, food parcels and other services. Conclusion Community health workers form the core of these teams and perform several health and psychosocial services in households and poor communities in South Africa, in addition to general health education. The teams studied provided a range of activities across many health conditions (mother and child related, HIV and TB, non-communicable diseases), as well as social services. These teams provided comprehensive care in a large-scale urban setting and can improve access to care.